Large-aperture Cu / SiO2 catalyst as well as preparation and application thereof

Through the process of dioxycyclohexanone synthesis, the problem of difficult to achieve both activity and selectivity of existing catalysts is solved, and efficient dioxycyclohexanone synthesis is achieved, which reduces production costs and is suitable for industrialization. application.

CN119186561AActive Publication Date: 2024-12-27ZHEJIANG UNIV OF TECH +1

Patent Information

Application Number
CN202411317532.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing catalysts are difficult to achieve both activity and selectivity in the synthesis of dioxycyclohexanone, and the production method is complex. The use of precious metals or chromium with high toxicity is not conducive to industrial application.

Method used

Using a large pore size Cu/SiO2 catalyst, the copper active component is supported on the macroporous silica by impregnation method, and Cu/SiO2 catalyst with a larger pore size is prepared, and dehydrolactide is used to dehydrolactide in diethylene glycol. Used in reactions, improve catalytic activity and selectivity through reduction pretreatment.

Benefits of technology

It significantly improves the selectivity of dioxycyclohexanone, reduces the production of by-products, reduces production costs, simplifies the preparation method of catalysts, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005052644210000081
    Figure BDA0005052644210000081
  • Figure HDA0005052644220000011
    Figure HDA0005052644220000011
Patent Text Reader

Abstract

The invention discloses a large-aperture Cu / SiO2 catalyst as well as preparation and application thereof. The large-aperture Cu / SiO2 catalyst comprises a carrier and copper oxides loaded on the inner surface and the outer surface of the carrier, the carrier is a large-aperture silicon dioxide carrier, in the large-aperture Cu / SiO2 catalyst, the mass percent of the carrier is 62.5%-99.5%, the mass percent of the copper oxides is 0.5%-37.5%, the large-aperture Cu / SiO2 catalyst is granular, the specific surface area is 150-300 m < 2 > / g, the pore volume is 0.8-1.2 ml / g, and the specific surface area of the large-aperture Cu / SiO2 catalyst is 20-30%. And the average pore size is 15-25nm. The invention provides the application of the large-aperture Cu / SiO2 catalyst in diethylene glycol dehydrogenation lactonization reaction, the selectivity of a target product is greatly improved finally, the production cost of the catalyst is low, the preparation method is simple and reliable, and the reaction conditions are mild.
Need to check novelty before this filing date? Find Prior Art

Description

(I) Technical field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a large-pore Cu / SiO2 catalyst, a preparation method thereof, and an application thereof in a dehydrogenation lactonization reaction of diethylene glycol. (II) Background technology

[0002] Para-dioxanone (PDO) is an important organic chemical product with a wide range of uses. It can not only be used directly as a fragrance and food additive, but also as a synthetic monomer for polydioxanone (PPDO). Polydioxanone can be used to make housings for electronic components to protect circuit boards and electronic components and improve the high temperature resistance of products. In the construction industry, it can be used to make building materials such as heat insulation, sound insulation, fire resistance and waterproofing to improve the service life and quality of buildings. In the automotive industry, it can be used to make automotive parts such as hoods and doors to improve the durability and safety of cars. In the chemical industry, it can be used as a manufacturing material for chemical equipment such as corrosion-resistant containers, pipes and valves. In the medical industry, it can be used to make surgical sutures, drug sustained-release materials, orthopedic fixation materials and tissue repair materials.

[0003] There are three methods for synthesizing dicyclohexanone: the first method is to use an organic synthesis method to synthesize dicyclohexanone using ethylene glycol, metallic sodium and chloroacetic acid as raw materials. This method is complicated to operate and has a high production cost, which is not conducive to industrial production.

[0004] The second method is the catalytic carbonylation reaction method: carbon monoxide, formaldehyde and 1,2-ethylene glycol or 1,3-dioxolane are used as raw materials for carbonyl addition to synthesize dioxanone. The catalysts used mainly include hydrogen fluoride, copper and silver carbonyl complexes.

[0005] The third method is a catalytic oxidative dehydrogenation cyclization method, which usually uses diethylene glycol as a reaction raw material for synthesis, and uses a transition metal such as copper, silver, platinum, zinc or a composite oxide catalyst of the above elements supported by an inert carrier such as alumina, activated carbon, silicon dioxide, etc. For example, US Pat. 2,142,033 uses a copper-chromium composite oxygenate catalyst (chromium content ≤ 5wt%) to obtain the target product by gas phase dehydrogenation lactonization of diethylene glycol, with a selectivity of 75.0%, but a yield of only 25%. US Pat. 2,807,629 increases the selectivity to 94.0% and the yield to 84% by changing the chromium content in the copper-chromium catalyst. US Pat. 3,119,840 also uses a copper-chromium catalyst. When the molar ratio of hydrogen to the raw material is 3 to 100, the yield of the target product dioxanone can reach up to 96%. Japanese Patent Laid-Open No. 58-99476 uses activated carbon, silicon dioxide or aluminum oxide to load platinum or palladium metal catalysts, and uses oxygen in the air as an oxidant to make diethylene glycol undergo oxidative dehydrogenation and self-condensation to synthesize p-dioxanone, but its selectivity can only reach 75% at most. Fetizon.M. et al. (Fetizon M, et al., Tetrahedron, 1975, 31, 171-176) used silver carbonate loaded on a diatomaceous earth carrier as a catalyst, and refluxed diethylene glycol in benzene for 10 hours, and the yield of p-dioxanone could reach 95%. In CN 1739852A, Wang Yuzhong et al. used a coprecipitation method to load copper, zinc and other alkali metal or alkaline earth metal compounds on an inert carrier, and the mass percentage of active components was 20-90%; the activity and selectivity of the catalyst were high, but the catalyst preparation process was relatively complicated, which was not conducive to industrial expansion of production.

[0006] It can be seen from the published literature that most catalysts cannot have both activity and selectivity, and the method for making the catalyst is still relatively complicated, using precious metal components or chromium with high toxicity, which is not conducive to its industrial application. The present invention loads the copper active component on macroporous silica by a simple impregnation method to obtain a macroporous Cu / SiO2 catalyst, does not add other chemical additives except the copper catalytic active substance, and in particular, the larger catalyst pore size facilitates the diffusion of raw materials and target product molecules, so that it not only has higher activity in the dehydrogenation lactonization reaction of diethylene glycol, but also can significantly reduce the generation of by-products, so that it also has higher selectivity. (III) Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a large-pore Cu / SiO2 catalyst and its preparation and application in the dehydrogenation lactonization reaction of diethylene glycol.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0009] In the first aspect, the present invention provides a large-pore Cu / SiO2 catalyst, wherein the large-pore Cu / SiO2 catalyst comprises a carrier and copper oxide loaded on the inner and outer surfaces of the carrier, wherein the carrier is a large-pore silica carrier, and the mass percentage content of the carrier and the active component in the large-pore Cu / SiO2 catalyst is as follows:

[0010] Carrier 62.5%~99.5%

[0011] Copper oxide 0.5%~37.5%

[0012] The large-pore Cu / SiO2 catalyst is in granular form with a specific surface area of ​​150 to 300 m 2 / g, the pore volume is 0.8~1.2ml / g, and the average pore diameter is 15~25nm.

[0013] Preferably, the macroporous Cu / SiO2 catalyst comprises the following components in weight percentage:

[0014] Carrier 70%~99%

[0015] Copper oxide 1%~30%.

[0016] In a second aspect, the present invention provides a method for preparing the large-pore Cu / SiO2 catalyst according to the first aspect, comprising the following steps:

[0017] (1) immersing the macroporous silica support in a mixed solution of a copper precursor and a complexing agent, and shaking and immersing for 1 to 48 hours;

[0018] (2) drying the mixture obtained in step (1) so that the copper precursor is evenly loaded on the inner and outer surfaces of the alumina carrier;

[0019] (3) placing the dried catalyst precursor obtained in step (2) into a muffle furnace for calcination in an air atmosphere, wherein the calcination conditions are: heating the temperature to 150-800°C at a heating rate of 0.5-20°C / min and calcining for 1-10h to obtain the large-pore Cu / SiO2 catalyst.

[0020] In the above preparation method, the large-pore silica carrier can be obtained by the following method: add 20-40 mesh commercial coarse-pore silica gel (type C silica gel) to a sodium hydroxide solution with a concentration of 0.4-0.7M and treat at 70-90°C for 7-9h, filter and wash with water until the filtrate is neutral, and then dry in a blast drying oven to obtain a large-pore silica carrier. The copper precursor can be a soluble copper salt such as copper nitrate, copper chloride, copper acetate, acetylacetonate copper, etc. The ligand is ammonia water, ethylenediamine, ethylenediaminetetraacetic acid or citric acid, and the molar ratio of the ligand to the copper precursor is 1-150:1, preferably 5-100:1. The drying treatment is carried out in a rotary evaporator and an oven, first drying at 10-60°C and 0.005-0.1MPa in a rotary evaporator for 1-24h, and then drying at 50-150°C in an oven for 1-48h. The calcination treatment conditions are preferably: heating to 300-600° C. at a heating rate of 3-15° C. / min and calcining for 2-6 hours.

[0021] In a third aspect, the present invention provides an application of the large-pore Cu / SiO2 catalyst described in the first aspect in the dehydrogenation lactonization reaction of diethylene glycol. Before the dehydrogenation lactonization reaction of diethylene glycol, the large-pore Cu / SiO2 catalyst needs to be pre-treated by reduction: at a space velocity of 100 to 800 h -1 A hydrogen-nitrogen mixed gas (v / v=1:1-9) is used as a reducing agent, and reduction is carried out under normal pressure and a temperature of 280-350° C. for 1-12 hours.

[0022] The catalyst of the present invention has a larger pore size, which is conducive to the diffusion of the raw material diethylene glycol with larger molecules and the product dioxanone inside the catalyst particles, which can not only improve the activity of the catalyst, but also reduce the residence time of the raw material diethylene glycol inside the catalyst pores, thereby significantly reducing the production of the main reaction byproduct 1,4-dioxane and other byproducts, and ultimately greatly improving the selectivity of the target product. Experimental results show that when the catalyst pore size is greater than 15nm, the selectivity of the target product is significantly improved; but when the catalyst pore size is too large (greater than 25nm), the dispersion of the active component Cu decreases and the particle size increases, resulting in an increase in other byproducts.

[0023] Preferably, the dehydrogenation lactonization reaction of diethylene glycol described in the present invention is carried out in a fixed bed reactor.

[0024] Preferably, the reaction conditions for the dehydrogenation of diethylene glycol are as follows: temperature of 220-280°C, reaction pressure of 0.1-1 MPa, liquid space velocity of the raw material of 0.2-1.5 h -1 , carrier hydrogen space velocity is 100~800h -1 .

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0026] (1) When the large-pore Cu / SiO2 catalyst provided by the present invention is used for preparing p-dioxanone by dehydrogenation lactonization of diethylene glycol, its larger pore size is conducive to the diffusion of the larger molecular raw material diethylene glycol and the product p-dioxanone inside the catalyst particles, which can not only improve the activity of the catalyst, but also reduce the residence time of the raw material diethylene glycol inside the catalyst pores, thereby significantly reducing the production of the main reaction by-product 1,4-dioxane and other by-products, and ultimately greatly improving the selectivity of the target product.

[0027] (2) The catalyst provided by the present invention has high activity and selectivity, low production cost, simple and reliable preparation method and relatively mild reaction conditions, which brings great advantages for the industrial application of the catalyst. (IV) Description of the drawings

[0028] Figure 1 Schematic diagram of a fixed bed reaction device used when the catalyst is applied to the dehydrogenation lactonization reaction of diethylene glycol: 1-hydrogen cylinder, 2-nitrogen cylinder, 3-raw material bottle, 4-high-pressure constant flow pump, 5-three-way valve, 6-pressure reducing valve, 7-stop valve, 8-mass flow meter, 9-check valve, 10-reaction tube, 11-reaction furnace, 12-condenser, 13 and 14-condensate inlet and outlet, 15-filter, 16-back pressure valve, 17-product collection tank, 18-catalyst bed. (V) Specific implementation methods

[0029] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0030] Example 1

[0031] 5 g of 20-40 mesh commercial coarse pore silica gel (C type silica gel, specific surface area 390 m 2 / g, pore volume 0.9cm 3 / g, average pore size 9.8nm) was added into 20ml of 0.6M sodium hydroxide solution and treated at 80℃ for 8h, filtered and washed with water until the filtrate was neutral, and then dried in a forced air drying oven at 110℃ for 24h to obtain a macroporous silica gel carrier.

[0032] Weigh 0.5703g of copper nitrate trihydrate, add it to 20ml of ammonia solution and wait for it to completely dissolve, then add 2g of the above-mentioned large-pore silica carrier and shake it at room temperature for 2h. Evaporate the solvent under reduced pressure at 60℃, place the evaporated catalyst precursor in a forced air drying oven at 110℃ for 4h, and then calcine it at 500℃ in a muffle furnace for 4h to obtain catalyst A. The weight content of CuO is 9.4%, and the rest is silica gel carrier. The specific surface area of ​​catalyst A is measured to be 240m 2 / g, pore volume 1.02cm 3 / g, average pore size 18.0nm.

[0033] Example 2

[0034] Preparation method of catalyst B Example 1, except that the mass of copper nitrate trihydrate added is 0.7604 g, and the obtained catalyst is recorded as catalyst B. The weight content of CuO is 12.5%, and the rest is silica gel carrier. The specific surface area of ​​catalyst B is measured to be 242 m 2 / g, pore volume 0.99cm 3 / g, and the average pore size is 17.8nm.

[0035] Example 3

[0036] Preparation method of catalyst C Example 1, but the amount of copper nitrate trihydrate added is 0.9505g, and the prepared catalyst is recorded as catalyst C. The weight content of CuO is 15.6%, and the rest is silica gel carrier. The specific surface area of ​​catalyst C is measured to be 245m 2 / g, pore volume 0.99cm 3 / g, and the average pore size is 17.5nm.

[0037] Example 4

[0038] The preparation method of catalyst D is the same as that of Example 1, except that the amount of copper nitrate trihydrate added is 1.1406 g, and the catalyst obtained is recorded as catalyst D. The weight content of CuO is 18.8%, and the rest is silica gel carrier. The specific surface area of ​​catalyst D is measured to be 246 m 2 / g, pore volume 0.98cm 3 / g, and the average pore size is 17.4nm.

[0039] Example 5

[0040] The preparation method of catalyst E is the same as that of Example 3, but the catalyst is calcined at 400°C. The catalyst obtained is recorded as catalyst E. The weight content of CuO is 15.6%, and the rest is silica gel carrier. The specific surface area of ​​catalyst E is 247m 2 / g, pore volume 0.98cm 3 / g, and the average pore size is 17.4nm.

[0041] Example 6

[0042] The preparation method of catalyst F is the same as that of Example 3, but the catalyst is calcined at 600°C. The catalyst obtained is recorded as catalyst F. The weight content of CuO is 15.6%, and the rest is silica gel carrier. The specific surface area of ​​catalyst F is 239m 2 / g, pore volume 1.01cm 3 / g, and the average pore size is 17.8nm.

[0043] Example 7

[0044] The preparation method of catalyst G is the same as that of Example 3, except that the temperature of treating the commercial macroporous silica gel with sodium hydroxide solution is 60°C. The catalyst obtained is recorded as catalyst G. The weight content of CuO is 15.6%, and the rest is silica gel carrier. The specific surface area of ​​catalyst G is measured to be 295m 2 / g, pore volume 1.08cm 3 / g, and the average pore size is 15.3nm.

[0045] Example 8

[0046] The preparation method of catalyst H is the same as that of Example 3, except that the temperature of treating the commercial macroporous silica gel with sodium hydroxide solution is 90°C. The catalyst obtained is recorded as catalyst H. The weight content of CuO is 15.6%, and the rest is silica gel carrier. The specific surface area of ​​catalyst H is measured to be 198m 2 / g, pore volume 0.95cm 3 / g, and the average pore size is 24.6nm.

[0047] Comparative Example 1

[0048] The preparation method of catalyst I is the same as that of Example 3, except that the temperature of the commercial coarse-pored silica gel treated with sodium hydroxide solution is 90°C and the treatment time is 12 hours. The prepared catalyst is recorded as catalyst I. The weight content of CuO is 15.6%, and the rest is silica gel carrier. The specific surface area of ​​catalyst I is measured to be 152 m 2 / g, pore volume 0.94cm 3 / g, and its average pore size is 29.8nm.

[0049] Comparative Example 2

[0050] The preparation method of catalyst J is the same as that of Example 3, except that the temperature of treating the commercial coarse-pored silica gel with sodium hydroxide solution is 50°C. The catalyst obtained is recorded as catalyst J. The weight content of CuO is 15.6%, and the rest is silica gel carrier. The specific surface area of ​​catalyst J is measured to be 327 m 2 / g, pore volume 1.05cm3 / g, and the average pore size is 13.6nm.

[0051] Comparative Example 3

[0052] The preparation method of catalyst K is the same as that of Example 3, except that the temperature of the commercial macroporous silica gel treated with sodium hydroxide solution is 30°C, and the concentration of the sodium hydroxide solution is 0.5M. The prepared catalyst is recorded as catalyst K. The weight content of CuO is 15.6%, and the rest is silica gel carrier. The specific surface area of ​​catalyst K is measured to be 345m 2 / g, pore volume 1.02cm 3 / g, and its average pore size is 11.8nm.

[0053] Comparative Example 4

[0054] The preparation method of catalyst L is the same as that of Example 3, but the silica gel carrier used is commercial coarse-pore silica gel (type C silica gel), and the prepared catalyst is recorded as catalyst L. The weight content of CuO is 15.6%, and the rest is silica gel carrier. The specific surface area of ​​catalyst L is measured to be 378m 2 / g, pore volume 0.88cm 3 / g, and the average pore size is 9.9nm.

[0055] Comparative Example 5

[0056] The preparation method of catalyst M is the same as that of Example 3, but the silica gel carrier used is commercial type B silica gel, and the prepared catalyst is recorded as catalyst M. The weight content of CuO is 15.6%, and the rest is silica gel carrier. The specific surface area of ​​catalyst M is measured to be 521m 2 / g, pore volume 0.70cm 3 / g, and the average pore size is 5.2nm.

[0057] Example 9

[0058] Reaction device such as Figure 1 As shown, the catalysts A, B, C, D, E, F, G, H, I, J, K, L and M prepared in the above examples and comparative examples are respectively loaded into the reaction tube of the fixed bed reactor, and the catalysts are first reduced under the following conditions: 320° C., normal pressure, hydrogen-nitrogen mixed gas (1:9, v / v) with a space velocity of 900 h -1 , the reduction time is 4h, and then the diethylene glycol dehydrogenation lactonization reaction is carried out. The reaction conditions are set as: 260℃, 0.1MPa, LHSV=0.5h -1 , carrier hydrogen space velocity 480h -1 , and the results are shown in the following table.

[0059] Table 1 Reaction performance of different catalysts in dehydrogenation of diethylene glycol

[0060]

[0061] [a]DEG-diethylene glycol; [b]PDO-p-dioxanone; [c]Diox-1,4-dioxane; [d]Mainly includes 2-(2-hydroxyethoxy)acetaldehyde, ethanol, etc.

[0062] It can be seen from the results in Table 1 that when the average pore size of the Cu / SiO2 catalysts (A~F) is in the range of 15~25nm, the catalysts not only have high activity but also have high selectivity for the target product; when the average pore size of the catalysts (J~M) drops below 15nm, although the catalyst activity does not change significantly, the selectivity of the by-product Diox and other by-products increases significantly; when the average pore size of the catalyst (I) is greater than 25nm, the feedstock conversion rate decreases significantly, and the selectivity of the target product PDO decreases.

Claims

1. A large-pore Cu / SiO2 catalyst, characterized in that: The large-pore Cu / SiO2 catalyst comprises a carrier and copper oxide loaded on the inner and outer surfaces of the carrier, wherein the carrier is a large-pore silica carrier. In the large-pore Cu / SiO2 catalyst, the mass percentage contents of the carrier and the active component are as follows: Carrier 62.5%~99.5% Copper oxide 0.5%~37.5% The large-pore Cu / SiO2 catalyst is in granular form with a specific surface area of ​​150 to 300 m 2 / g, the pore volume is 0.8~1.2ml / g, and the average pore diameter is 15~25nm.

2. The macropore Cu / SiO2 catalyst according to claim 1, characterized in that: The macroporous Cu / SiO2 catalyst comprises the following components in weight percentage: Carrier 70%~99% Copper oxide 1%~30%.

3. A method for preparing a large-pore Cu / SiO2 catalyst as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) immersing the macroporous silica support in a mixed solution of a copper precursor and a complexing agent, and shaking and immersing for 1 to 48 hours; (2) drying the mixture obtained in step (1) so that the copper precursor is evenly loaded on the inner and outer surfaces of the alumina carrier; (3) placing the dried catalyst precursor obtained in step (2) into a muffle furnace for calcination in an air atmosphere, wherein the calcination conditions are: heating the temperature to 150-800°C at a heating rate of 0.5-20°C / min and calcining for 1-10h to obtain the large-pore Cu / SiO2 catalyst.

4. The preparation method according to claim 3, characterized in that: The copper precursor is a soluble copper salt, the complexing agent is ammonia water, ethylenediamine, ethylenediaminetetraacetic acid or citric acid, and the molar ratio of the complexing agent to the copper precursor is 1-150:

1.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the complexing agent to the copper precursor is 5-100:

1.

6. The preparation method according to claim 3, characterized in that: The drying treatment is carried out in a rotary evaporator and an oven, first drying for 1 to 24 hours at 10 to 60° C. and 0.005 to 0.1 MPa in the rotary evaporator, and then drying for 1 to 48 hours at 50 to 150° C. in an oven.

7. The preparation method according to claim 3, characterized in that: The calcination treatment conditions are: heating to 300-600°C at a heating rate of 3-15°C / min and calcining for 2-6h.

8. Use of the macroporous Cu / SiO2 catalyst as claimed in claim 1 or 2 in the dehydrogenation lactonization reaction of diethylene glycol, wherein before the dehydrogenation lactonization reaction of diethylene glycol, the macroporous Cu / SiO2 catalyst needs to be pre-treated by reduction: at a space velocity of 100 to 800 h -1 The hydrogen-nitrogen mixed gas is used as the reducing agent, and the reduction is carried out under normal pressure and a temperature of 280-350°C for 1-12 hours.

9. The use according to claim 8, characterized in that: The diethylene glycol dehydrogenation lactonization reaction is carried out in a fixed bed reactor.

10. The use according to claim 8, characterized in that: The reaction conditions of the dehydrogenation of diethylene glycol are as follows: temperature of 220-280°C, reaction pressure of 0.1-1 MPa, liquid space velocity of the raw material of 0.2-1.5 h -1 , carrier hydrogen space velocity is 100~800h -1 .

Citation Information

Patent Citations

  • Catalyst for preparing p-cyclodexanone dioxide

    CN1739852A

  • Preparation of 2-p-dioxanone

    JP1983099476A

  • Catalyst for preparing p-dioxanone and method for preparing p-dioxanone

    CN112473675A

  • Copper-based catalyst for preparing ethylene glycol by oxalate hydrogenation and preparation method thereof

    CN112588290A

  • Mesoporous silica confined copper-based catalyst with hydrogen enrichment effect as well as preparation method and use method of mesoporous silica confined copper-based catalyst

    CN114950426A

Cited By

  • Heteroatom modified SiO2 supported copper oxide catalyst as well as preparation method and application thereof

    CN120361911A